Psychological and behavioural determinants in type 2 diabetes self-management: A scoping review - Sari, Nurul Ratna; Haryanto, Haryanto; Suriadi, Suriadi (JOURNAL OF Mental Health Concerns, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic disease with a continuously increasing prevalence both globally and nationally. Successful management of T2DM is highly dependent on patient self-management behaviors. Assessment tools such as the Diabetes Self-Management Questionnaire-Revised (DSMQ-R) and the Summary of Diabetes Self-Care Activities-Indonesia (SDSCA-I) have been widely used to assess independent diabetes management. However, the integration of these tools with the Indonesian Nursing Diagnosis Standards (INDS) in establishing nursing diagnoses is still limited. Purpose: To map the existing scientific evidence regarding the use of DSMQ-R and SDSCA-I in assessing diabetes self-management and to explore their potential in supporting nursing diagnosis formulation based on INDS. Method: A scoping review was conducted following the PRISMA-ScR guidelines. Literature searches were performed in Google Scholar, PubMed, and ScienceDirect for articles published between 2018 and 2025. Included studies were primary quantitative and mixed-methods research addressing DSMQ-R, SDSCA, self-management in Type 2 Diabetes Mellitus, and their correlation with clinical outcomes. Results: Most studies demonstrated that DSMQ-R and SDSCA have good validity and reliability and are significantly correlated with glycemic control (HbA1c). DSMQ-R showed a stronger correlation with HbA1c compared to SDSCA. However, no studies were identified that directly integrated these instruments with INDS in establishing nursing diagnoses. Conclusion: DSMQ-R and SDSCA-I have the potential to serve as foundational tools for developing INDS-based assessment models in nursing practice. Keywords: DSMQ-R; INDS; SDSCA-I; Self-Management; Scoping Review; Type 2 Diabetes Mellitus.